Internationalization in higher education: Motives, challenges, support options, and work study balance on WHO-5 wellbeing among international students in Hungary - Daniel Kibet Koech; Esayas Demissie Degago; Lavender Awino Okore; Edina Molnár (Acta Psychologica)
The rate at which students in universities abroad are blending their studies with work calls for an in-depth investigation to find out if indeed it is possible to balance work, studies and social life and whether it leads to the attainment of WHO-5 well-being goals. This study investigates the motives, challenges, available support options, and impact of work-study life balance on WHO-5 general well-being among international students studying in Hungary.125 respondents obtained through random sampling in social media groups of international students were subjected to an online survey. Descriptive and regression analysis was done using SPSS while psychological well-being was measured using the WHO-5 questionnaire. Findings indicate that work-study balance significantly and positively contributed to an average WHO-5 Wellbeing index among international student workers. It was also discovered that motives for working while studying also significantly and positively affect the WHO-5 wellbeing of international students. Higher education institutions and employers should develop policies, frameworks and functioning counselling systems with critical consideration of factors that drive students to engage in employment while working abroad. Special counselling units within multicultural institutions should be established to offer real-time social support to protect international students from stressors arising from an unfamiliar environment that pushes them into depression. Timely access to counselling services will enable international students to achieve healthier WHO-5 well-being.